The Construction of Isomorphic Physics (FORFIS) as Gamification-Based Application to Support Online Learning - Desy Kumala Sari; Pri Ariadi Cahya Dinata; Supahar Supahar (JIPF (Jurnal Ilmu Pendidikan Fisika), 2022)
The learning process during the Covid-19 pandemic becomes monotonous and make students tired. Therefore, there is needed for a learning media based on gamification that can support online learning. This research was conducted to develop an android application that can be used in physics learning, especially in momentum and impulse materials. This program is an application based on gamification and more attractive for students. The developed application is called Physics Isomorphic (FORFIS). This research uses the ADDIE model (Analysis, Design, Develop, Implementation, and Evaluation) as development phases. The research data were obtained from a questionnaire containing 27 statements and analyzed using the ideal standard deviation score. The mean score result by expert judgement is 132.29, which is in the "excellent" category. The Application of Isomorphic Physics (FORFIS) is declared feasible to be used as a medium of physics learning.